STUDI ANALISIS GOVERNOR SEBAGAI LOAD FREQUENCY CONTROL PADA PLTG MENGGUNAKAN FUZZY LOGIC CONTROLLER - Aryanata, Gusti Made Ngurah Christy; Suweden, I Nengah; Mataram, I Made (Jurnal Teknologi Elektro; Vol 17 No 1 (2018): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2018)
A good electrical power system is a system that can serve the load in a sustainable and stable voltage and frequency. Changes in frequency occur due to the demand of loads that change from time to time. The frequency setting of the PLTG power system depends on the active power charge in the system. This active power setting is done by adjusting the magnitude of the generator drive coupling. The frequency setting is done by increasing and decreasing the amount of primary energy (fuel) and carried on the governor. Simulation in governor analysis study as load frequency control at PLTG using fuzzy logic controller is done by giving four types of cultivation that is 0,1 pu, 0,2pu, 0,3 pu and 0,4 pu. The simulation is done to compare the dynamic frequency response output and the resulting stability time using fuzzy logic controller with PI controller. Based on the results of comparative analysis conducted to prove that governor as load frequency control using fuzzy logic control is better than using PI controller. This can be seen from the output response frequency and time stability.